EFFECT OF COMPREHENSIVE STRATEGIES FOR PREVENTION OF VENTILATOR-ASSOCIATED PNEUMONIA ON INCIDENCE OF THE DISEASE IN HOSPITALIZED PATIENTS IN INTENSIVE CARE UNITS - Khadijeh Nasiriani; Mohammad Hossein Jarahzadeh; Maryam Souroush (Journal of University Medical & Dental College, 2017)
ABSTRACT: INTRODUCTION: Ventilator-associated pneumonia (VAP) is the second most common nosocomial infection and the commonest infection in intensive care units. VAP is associated with prolonged hospitalization, high mortality rate and treatment cost. The present study aimed to determine the impact of the implementing comprehensive strategies for prevention of ventilatorassociated pneumonia on incidence of the disease in hospitalized patients in intensive care units. METHODS: This was a randomized clinical trial on 86 ventilated patients in intensive care unit. The participants were divided into two groups: control and treatment. Treatment group received comprehensive strategies for prevention of ventilator-associated pneumonia. Control group received routine care. Data collection form consisted of demographic and clinical data as well as "Modiﬁed Clinical Pulmonary Infection Score (MCPIS) .The collected data was analyzed using SPSS 20 (descriptive statistical analysis and analysis of variance with repeated measurements). RESULTS: The results of the study by the third day showed that mean score of MCPIS was not statistically signiﬁcant in both groups (P > 0.05). Mean score of MCPIS was signiﬁcantly lower in the treatment group than the control group on the fourth and ﬁfth days of the project (P < 0.05). Trend of incidence of pneumonia was not signiﬁcant in the treatment group over time (P > 0.05) but statistically signiﬁcant in the control group (P< 0.05). CONCLUSION: The results of implementation of comprehensive strategies for prevention of VAP decreased the incidence of ventilator-associated pneumonia in the patients hospitalized in intensive care unit. Therefore, it is recommended that infection control authorities and critical care nurses should use comprehensive prevention strategies in order to reduce the incidence of VAP.